The Impact of Knowledge Management on Human Resource Productivity through Cultural Capital and Social Capital (Case Study: Islamic Azad University, Isfahan Branch) - Abbas Ghaedamini Harouni; Reza Ebrahimzadeh Dastjerdi; Majed Maharani Barzani; Mehrdad Sadeghi de cheshmeh (Allameh Tabataba'i University Press, 2018)
The purpose of this study was to determine the impact of knowledge management on human resource productivity through cultural capital and social capital (Case study: Islamic Azad University, Isfahan Branch). The purpose of the present study is to determine the purpose of the study and to collect the descriptive correlational data. The statistical population of this study consisted of all the staff of Islamic Azad University of Isfahan with 1000 students who were selected through Cochran sampling formula 287 as sample size by stratified sampling method. (Hershey & Goldsmith (1980) and Narapitoguchal Social Capital questionnaire, 1980), and Bourdieu Cultural Capital standard questionnaire (1999). The validity of the questionnaires was assessed based on content, formal and construct validity. And after the necessary terms, the validity of the case The reliability of the questionnaires was estimated 0.90, 0.91, 0.88, and 0.89, respectively, and the data were analyzed at the inferential level including structural equation modeling. The results showed that knowledge management through cultural capital has a positive and significant effect on human resource productivity which has a coefficient of 0.25 and social capital has a significant and positive effect on human resource productivity. It is 0.66 and also the direct impact of knowledge management on human resource productivity has a positive significant coefficient of 0.88.